Stockhausen 1: Chöre für Doris- Choral- Drei lieder - Sonatine - Kreuzspiel - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2002)
CHÖRE für DORIS / CHORUSES for DORIS for choir a cappellaCHORAL for choir a cappella DREI LIEDER / THREE SONGS for alto voice and chamber orchestraSONATINE for violin and pianoKREUZSPIEL / CROSS-PLAY for oboe, bass clarinet, piano, 3 percussionists.